A randomized, double-blind, placebo controlled safety, tolerability, and pharmacokinetic dose escalation study of a gentamicin vancomycin gel in patients undergoing colorectal surgery. Issue 1 (December 2016) - Bennett-Guerrero, Elliott; Minkowitz, Harold; Segura-Vasi, Alvaro; Marcet, Jorge; White, Jennifer; Corey, G; Allenby, Kent
Abstract Background Despite numerous interventions promulgated by the Surgical Care Improve Project (SCIP) and other organizations, surgical site infection (SSI) continues to be a significant medical problem. DFA-02 is a novel bioresorbable modified-release gel consisting of both gentamicin (16.8 mg/mL) and vancomycin (18.8 mg/mL) to be applied during surgical incision closure for the prevention of SSIs. The following double-blind phase 2a trial was designed to test the safety and tolerability of DFA-02. Methods At six US sites, the study planned to randomize 40 subjects undergoing colorectal surgery (30 with DFA-02, and eight with placebo gel) in four ascending dose cohorts (10-, 20-, 30-, and 40-mL study drug per wound). Safety was ascertained and serum pharmacokinetics (PK) was determined. Results Study enrollment was discontinued after the first three dose cohorts (10, 20, and 30 mL) as even very large incisions could not accommodate more than 20 mL of gel, leaving no scientific justification for the 40-mL cohort. DFA-02 was well tolerated and showed no evidence of local tissue reaction or impairment of wound healing. No serious AEs were deemed related to study drug. Systemic exposure to gentamicin and vancomycin remained well below levels considered to be at higher risk for oto- or nephrotoxicity. The maximal gentamicin and vancomycin levels observed were 2.36 and 0.684 μg/mL at 6 h, which were well below the prespecified stopping criteria of 12 and 20 μg/mL, respectively. Conclusions In this small phase 2a study, the study drug was well tolerated and appeared to be free of serious adverse effects. Consistent with these findings, the PK values were consistent with gradual release of the antibiotics from the gel in the surgical site. Trial registration ClinicalTrials.gov, NCT01496352